2013
DOI: 10.1017/s0033291713001414
|View full text |Cite
|
Sign up to set email alerts
|

Common variation inNCAN, a risk factor for bipolar disorder and schizophrenia, influences local cortical folding in schizophrenia

Abstract: This study is the first to describe an effect of the NCAN risk variant on brain structure. Our data show that the NCAN risk allele influences cortical folding in the occipital and prefrontal cortex, which may establish disease susceptibility during neurodevelopment. The findings suggest that NCAN is involved in visual processing and top-down cognitive functioning. Both major cognitive processes are known to be disturbed in schizophrenia. Moreover, our study reveals new evidence for a specific genetic influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 69 publications
1
52
0
Order By: Relevance
“…NCAN is a brain-specific chrondoitin sulfate proteoglycan (CSPG), which is mainly expressed during early brain development (http://www.informatics.jax.org/assay/MGI: 4826610, Schultz et al, 2014). It is widely expressed throughout the mammalian brain, including subcortical structures, such as the hippocampus and the amygdala (Cichon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NCAN is a brain-specific chrondoitin sulfate proteoglycan (CSPG), which is mainly expressed during early brain development (http://www.informatics.jax.org/assay/MGI: 4826610, Schultz et al, 2014). It is widely expressed throughout the mammalian brain, including subcortical structures, such as the hippocampus and the amygdala (Cichon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In an early imaging genetics study, Schultz et al (2014) demonstrated that NCAN rs1064395 genotype influenced cortical folding in the occipital and prefrontal cortex. The authors hypothesized that this may establish disease susceptibility during neurodevelopment .…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression of DNA-methyltransferase-1 in GABAergic interneurons in the frontal cortex of SZ and BD subjects results in decreased expression of glutamic acid decarboxylase (GAD 67 ), brain-derived neurotrophic factor (BDNF), and extracellular matrix (ECM) proteoglycans like reelin and chondroitin sulfates (Berretta, 2012;Dong et al, 2014). The NCAN gene, which encodes a brain-specfic chondroitin sulfate, also is a risk factor for both SZ and BD (Schultz et al, 2014;Raum et al, 2015). The relationships between altered ECM function and structural myelin lipid changes still remains to be determined in SZ and BD.…”
Section: Discussionmentioning
confidence: 99%
“…An association between schizophrenia and a common variation of neurocan, a developmentally regulated CSPG recognized as a component of PNNs (Celio et al, 1998;Deepa et al, 2006), was recently found in a genome-wide association study (Muhleisen et al, 2012). A subsequent study combining genetic analysis and magnetic resonance imaging identified a correlation between this risk allele and altered cortical folding in schizophrenia patients, suggesting that neurocan might play a role in aberrant brain development underlying this psychiatric disorder (Schultz et al, 2014). Furthermore, the neurocan risk allele has been associated with hyperactivity in a group of patients with schizophrenia, major depression, and bipolar disorder (Miro et al, 2012).…”
Section: Pnns and Schizophreniamentioning
confidence: 94%